Net energy metering scheme with and without battery storage analysis - Yeng, Kok Ping (2022)
The Net Energy Metering (NEM) scheme is introduced throughout Malaysia promoting consumers' interest in photovoltaic (PV) installation. PV generated kWh will be exported to the utility grid and credited to their monthly bill which will be "net" of the amount of electricity imported from the grid. Consumers are also able to explore further with the combination of battery storage allowing consumers to utilize the excess generated electricity. Most of the analysis in solar PV concentrates on residential consumers, in this analysis, the main focus will be a larger development with real-time load studies in the feasibility of NEM without and with battery storage installation based on the government's latest implementation of NEM 3.0 "Net Offset Virtual Aggregations (NOVA) Programme". In general, installing battery storage can utilize the excess generated electricity to store into the battery storage and use it at their will, reducing their reliance on utility grid supply. Most of the commercial buildings are charged by Tenaga Nasional Berhad (TNB) with monthly maximum demand (MD) charges, the battery storage will provide a solution to consumers in reducing the MD and thus, the monthly electricity bills. The analysis is based on a shopping mall commercial building, applied meter charges under Tariff C1. A compiled data of the monthly electricity bills is collected and analyzed in terms of the consumption, and the MD. The shopping mall has a wide footprint at the rooftop which is currently used as open space parking and M&E plant room. The proposed solar PV shall be installed elevated with steel structures support. It is expected that upon installation the development will be able to reduce their current monthly MD consumption and lower down the electricity bill. In conclusion, the consumer able to enjoy profit and saving with solar PV installation, however, with installation of battery storage system, the cost and return of investment is too long and only applicable with proper scheduling to the consumer's load profile. As battery lifespan decreases depending on the usage, replacement is required every few years. If the battery storage installation is without proper scheduling, the consumer will not be benefited from the installation and require to pay hefty cost throughout the years. Nevertheless, the consumer with solar PV under NEM NOVA able to enjoy the benefits even after 10 years of the scheme changes to SELCO.